PENGARUH EFEKTIFITAS SATUAN PENGENDALIAN INTERN DAN KOMITMEN ORGANISASI TERHADAP PENCAPAIAN GOOD UNIVERSITY GOVERNANCE PADA UNIVERSITAS TADULAKO PALU - Betty, Betty (Katalogis, 2016)
The purpose of this research are; 1) to determine the effectiveness of the internal control unit, organizational commitment and good university governance at Tadulako University Palu, 2) to know and analyze the simultaneous effect of the effectiveness of the internal control unit, organizational commitment to good university governance at Tadulako University Palu, 3) to know and analyze the effectiveness of the internal control unit of the good university governance at Tadulako University Palu, 4) to know and analyze the influence of organizational commitment to good university governance at Tadulako University Palu. This research was a quantitative research with explanatory research approach. The sampling teqnique used incidental sampilng with 88 respondents. The research results showed that 1) the effectiveness of the internal control unit and organizational commitmenthave significant effect simultaneously towards the achievement of good university governance, 2) the effectiveness of the internal control uni have significant effect partially to the achievement of good university governance, 3) the organizational commitment have significant effect partially to the achievement of good university governance at Tadulako Universitas Palu.